Swim fin design utilizing principles of marine animal locomotion - Lewis, E. R.; Lorch, D. (Swimming III. Proceedings of the Third International Symposium of Biomechanics in Swimming, University of Alberta, Edmonton, Canada, 1979)
The purposes of this investigation were: 1) to determine the mechanical efficiency of commercially available swim fins in order to evaluate the feasibility of design improvements, and 2) to make several design changes to fins, utilizing principles of marine animal locomotion, and to compare swimming performances with these new fms with performances with commercial fins.